Pre-Weichselian Quaternary glaciations of the British Isles, The Netherlands, Norway and adjacent marine areas south of 68°N: Implications for long-term ice sheet development in northern Europe: - Lee, J.R.; Busschers, F.S.; Sejrup, H.P. (2012)
Within this paper we review the pre-Weichselian glacial history of northern Europe focussing on evidence from the British Isles, Netherlands, Norway and adjacent marine areas that record the activity of the British (BIS) and Scandinavian (SIS) ice sheets. The objective of the paper is to examine the long-term evolution of the two ice sheets in order to determine their level of synchronicity and their relationship to the Plio-Pleistocene record of Northern Hemisphere Glaciation. Geological evidence demonstrates striking long-term similarities between the behaviour of the BIS and SIS, with a step-wise intensification in the glacial signal: (1) first Ice Rafted Debris (IRD) input onto the continental margin at ca 2.7-2.6 Ma and restricted glaciation prior to ca 1.1 Ma; (2) initiation of more lowland-style glaciation from 1.1 Ma; (3) repeated shelf-edge glaciations from 0.45 Ma. These 'steps' coincide with a major intensification of the Northern Hemisphere climate signal at the beginning of the Quaternary, and the Mid Pleistocene Transition. Temporal and spatial variabilities in the behaviour of different sectors of the BIS and SIS appear to reflect regional-scale geographic (latitude, elevation), climatic (moisture, temperature) and glaciological (deformable beds) controls that modulate the build-up of ice volume in the main ice accumulation areas relative to global climate forcing and its subsequent lateral expansion. © 2010 NERC.